A Conceptual Study of Electric Vehicle Market in India - B M Honna Prabhu Lingegowda; Dr. A N Santosh Kumar (International Journal of Engineering and Management Research, 2022)
Research into electric vehicles (ev) as a potential means of reducing the greenhouse effect is extensive. Thanks to improvements in power electrics, energy storage, and support, the plug-in hybrid electric vehicle (phev) offers competitive driving range and fuel economy when compared to vehicles powered by internal combustion engines (icev).the various sorts of evs' operational procedures will be detailed in this review study. We'll also talk about battery and supercapacitor technology as potential ways to boost phevs' energy capacity.